EVOLUTION OF THE SUSTAINABLE DEVELOPMENT PARADIGM AND TRANSFORMATION OF MULTILEVEL GOVERNANCE MODELS UNDER EXOGENOUS CHALLENGES (INNOVATIVE ECONOMY, 2026)
Kramarchuk S.P. EVOLUTION OF THE SUSTAINABLE DEVELOPMENT PARADIGM AND TRANSFORMATION OF MULTILEVEL GOVERNANCE MODELS UNDER EXOGENOUS CHALLENGESPurpose. The aim of the study is to generalize and systematize the evolution of managerial models for the implementation of sustainable development and to identify structural gaps between global and national practices of their implementation.Methodology of research. The study applies methods of theoretical generalization and systematization to identify the evolutionary stages of sustainable development. Institutional analysis was used to assess the level of coordination among governance actors, while the comparative method enabled the comparison of global and national practices. Content analysis of strategic documents ensured the formation of a benchmark model of sustainable development. The key research tool is a matrix approach, on the basis of which a matrix of structural gaps and a second-level matrix reflecting the transformation of the sustainable development system under exogenous shocks were constructed. This approach provides for the integration of indicator-based, institutional, and adaptive dimensions of governance and makes it possible to assess the degree of coherence between different levels of sustainable development policy implementation.Findings. The study summarizes the evolution of the concept of sustainable development and systematizes the main managerial models of its implementation at the global and national levels. Five stages of transformation of the sustainable development management paradigm were identified: environmental correction, integration, strategic institutionalization, transformational governance, and resilient recovery. It is substantiated that the contemporary model of sustainable development is based on multilevel, polycentric, and adaptive governance using ESG approaches, digital monitoring, and green finance mechanisms. It is proven that under wartime challenges in Ukraine, the formation of an adaptive multilevel coordination system focused on ensuring economic resilience and implementing the principles of “green recovery” becomes of crucial importance. The study reveals the existence of a methodological gap between the development of indicator systems for assessing sustainable development and the practice of their integrated application in strategic management. On this basis, the expediency of using benchmarking and matrix analysis tools to improve the effectiveness of sustainable development governance is substantiated.Originality. A multi-level matrix approach to the analysis and transformation of the sustainable development system has been developed, ensuring the integration of structural gap diagnostics with mechanisms for overcoming them under conditions of exogenous shocks. It has been proven that martial law acts not only as a destabilizing factor, but also as a catalyst for the transition to a resilient development model, thereby transforming the logic of the functioning of the inter-level governance system. Within the proposed approach, indicator-based, institutional, and adaptive dimensions of governance are integrated, making it possible to ensure the comprehensiveness of assessment and the coherence of managerial decisions across different levels of sustainable development policy implementation.Practical value. The proposed approaches can be used by public authorities, regional institutions, and business entities to develop sustainable development strategies, improve the system of inter-level coordination, and enhance the effectiveness of managerial decision-making under crisis conditions. The research findings can be applied in the development of Ukraine’s post-war recovery programs, the implementation of ESG approaches, sustainable development monitoring systems, and benchmarking mechanisms for evaluating governance effectiveness at the national, regional and corporate levels.Key words: sustainable development, sustainable development governance, multilevel governance, adaptive governance, resilience, ESG, green finance, benchmarking, strategic management, post-war recovery of Ukraine.
Keywords: sustainable development; sustainable development governance; multilevel governance; adaptive governance; resilience; ESG; green finance; benchmarking; strategic management; post-war recovery of Ukraine